Translating Cultural Terms in Tourism: Strategies Used by Translators - Kim, A. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
The purpose of the research is to explore the strategies used by translators when translating cultural terms found in tourism materials. Cultural terms, intertwining deeply with local customs, traditions, and social values, often pose translation challenges since no direct equivalents exist within the target language. Such difficulties can result in poor accuracy and cultural sensitivity in the translation processes. Using a qualitative approach, the study draws on semi-structured interviews with nine experienced translators working in the tourism sector. The collected data was analyzed by using thematic analysis to identify recurring themes related to translation practices, challenges, and contextual considerations. The findings highlight a predominant use of hybrid strategies, which involve retaining original cultural terms while providing contextual explanations to enhance understanding for the target audience. The thesis presents insights into how translators navigate linguistic and cultural complexities when translating for diverse audiences.
Keywords: cultural terms, tourism translation, translation strategies, hybrid translation, translator decision-making